Strengthening Zakat Management in Afghanistan: Lessons from Indonesian and Malaysian Legal Frameworks - Abdulhaleem Obaid A. Alyusufi; Ghulam Mustafa Nukhba; JM. Muslimin; Syahrul Ramadhan Hidayat (Faculty of Shariah and Law, UIN Syarif Hidayatullah Jakarta, 2024)
This research aims to analyse the contextualization of the best practices of zakat management models from Indonesia and Malaysia in Afghanistan to enhance zakat effectiveness. The study employs a comparative analysis of successful practices in both countries, focusing on their applicability to Afghanistan's context. Findings indicate that adopting elements from Indonesia's community participation and Malaysia's centralized approach can improve transparency and efficiency in zakat management. The research concludes that Afghanistan must develop a comprehensive legal framework, establish a national zakat authority, and raise public awareness to overcome existing challenges. By integrating these strategies, Afghanistan can maximize zakat's potential to reduce poverty and promote social justice.